Effectiveness of a Self-Regulated Learning Model on Academic Procrastination Among Chinese University Students - Fangyuan, Liu; Chularut, Pasana; Kambhunaayudhaya, Paradee (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed (1) to evaluate the effectiveness of a structured SRL intervention in reducing academic procrastination after implementation and (2) to compare its effectiveness between experimental and control groups during and after the intervention period. A quasi-experimental design was conducted with 90 first-year undergraduates randomly assigned to an experimental group (n = 45) and a control group (n = 45). No significant baseline differences were found between groups. The experimental group received a 12-week SRL intervention, whereas the control group continued traditional instruction. Academic procrastination was measured using a validated 26-item scale covering six dimensions—Fear of Failure, Difficulty in Deciding, Task Aversiveness, Rebellion Against Control, Dependency, and Risk-Taking—at pre-test, post-test, and four-week follow-up. Based on the repeated-measures ANOVA, the key findings were as follows: 1) The experimental group showed significant reductions in overall academic procrastination from pre-test (M = 3.88) to post-test (M = 2.82) and follow-up (M = 2.73) (p < .001), with decreases observed across all six dimensions. 2) Significant interaction effects between time and group indicated that these reductions in the experimental group were significantly greater than those in the control group, whose scores remained consistently high (pre-test M = 3.98; follow-up M = 3.92). The largest between-group differences emerged in dependency, risk-taking, and fear of failure. The findings extend the applicability of the Self-Regulated Learning Model to the Chinese higher education context and provide empirical evidence that structured SRL programs can systematically reduce multidimensional academic procrastination among undergraduate students.